The House of the Wolfings : A Tale of the House of the Wolfings and All the Kindreds of the Mark Written in Prose and in Verse - Morris, William, 1834-1896 (Salt Lake City, UT : Project Gutenberg, 2001)
"The House of the Wolfings" by William Morris is a fantasy novel published in 1889. Written in a blend of prose and verse, it portrays Germanic Gothic tribes defending their homeland against the armies of imperial Rome. The story follows Thiodolf, a war leader whose fate becomes entwined with a cursed dwarf-made mail-shirt and the divine women who support him. Considered a pioneering work that united historical settings with supernatural elements, it directly influenced J.R.R. Tolkien's "The Lord of the Rings" and helped establish modern fantasy literature. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_House_of_the_Wolfings
Release date is 2001-10-01
Transcribed from the 1904 Longmans, Green, and Co. edition by David Price
Keywords: Fantasy fiction